An Antenna Integrated Low-Noise Receiver for mm-Wave Wideband, High-Datarate Communication - Campion, James (My University, 2015)
The continued growth in mobile network data traffic, forecast to increase at a compound rate of 54% annually, has created the need for wireless networks which can handle data rates orders of magnitude greater than is possible with current systems. This growth in data traffic necessitates the use of advanced techniques such as carrier-aggregation and MIMO in order to increase the capacity of wireless networks. In spite of these techniques, current wireless networks are insufficient to handle the predicted future levels of data traffic as their capacity is inherently limited by their narrow bandwidth. This dilemma has led to a surge in interest in the creation of wireless links at carrier frequencies far higher than currently used, where wide swathes of continuous bandwidth are readily available. One such band of frequencies, known as the H-band, lying between 200-325 GHz, has recently been allocated for use in wireless communication links by the Federal Communications Commission in the United States of America. The development of compound semiconductor materials, such as Indium Phosphide (InP), and advances in fabrication and processing techniques over the course of the past decade has enabled the creation of solid-state circuits at such frequencies. To date, many front-end low-noise amplifiers (LNAs) targeting H-band frequencies have reported noise figures of the order of 10 dB, with only moderate values of gain, thereby limiting the potential capacity of receiver systems. In light of this, this thesis presents the design of a mixer-first receiver for use at H-band frequencies which contains no front-end RF amplifier. Instead, the proposed receiver utilises a single-balanced topology consisting of an input RF quadrature hybrid, a single-balanced transconductance mixer, a pair of IF amplifiers and an active IF balun to perform down-conversion and amplification. An antenna is also integrated on chip to provide the input RF signal. The proposed receiver has IF and RF bandwidths of 42 and 138 GHz respectively and requires only 0 dBm of LO drive power to operate. Careful co-design of the transconductance mixer and IF amplifier ensures wideband IF operation of the receiver. The total conversion gain of the receiver is 23 dB and the simulated noise figure is between 13-15 dB over the entire IF bandwidth. The theoretical capacity of the receiver is somewhat greater than previously reported H-band receiver designs as a result of its wide IF bandwidth. The receiver is implemented using the TSC 250 InP double-heterojunction bipolar transistor (DHBT) process from Teledyne Scientific Corporation and consumes an area of 0.9x1.19 mm2. The design of each component of the receiver is presented, as well as a discussion of the trade-offs made in the design of the complete receiver, followed by a characterisation of the complete receiver and discussion of its performance.
Keywords: Elektronik; Informations- och kommunikationsteknik; Electronics; Information & Communication Technology